Spectrum of Acute Kidney Injury in a Nephrology Unit - Naureen Chaudhri , Mirza Naveed Shehzad, Mamoon Akbar Qureshi, Mariam Masud, Naureen Chaudhri , Mirza Naveed Shehzad, Mamoon Akbar Qureshi, Mariam Masud (Journal of Rawalpindi Medical College, 2019)
Background: To identify etiologic factors causing acute kidney injury (AKI) in our local population that were admitted to tertiary care nephrology unit over one year duration. Methods: In this prospective cohort study adult patients with elevated serum creatinine, evaluated at least twice,were included. Workup for glomerulonephritis included complements levels, ANA, Anti dsDNA, ANCA,AntiGBM, SPEP. Renal biopsy was performed for suspected RPGN/Vasculitis, AIN, unexplained AKI.Renal replacement therapy was initiated for standard indications. Decreased renal perfusion was diagnosed when blood pressure was less than 90/60 mmHg, signs of volume depletion and severe cardiac failure. Urine output less than 400ml/day was taken as oliguria. The AKI definition and diagnosis was based on RILFE criteria ,i.e, an abrupt (1 to 7 days) and sustained (more than 24 hours) decrease in kidney function. Results: Majority (62%) were male. Majority of the patients (87.1%) were in failure category. Infection/sepsis was the most common etiology (44.6 %), followed by drugs (10.5%),gastroenteritis (10.2%),surgical cases (8.8%) and obstructive nephropathy (7.5 %). Mortality was 39.1%, reflecting critical condition and markedly deranged renal function. Conclusion: AKI is a major public health challenge. It is associated with high morbidity and mortality. Infection/sepsis is the predominant etiological factor causing AKI in our patients. Combating infections/communicable diseases is crucial in preventing AKI